Analisis Komparatif Saham Sektor Pertambangan pada Indeks LQ45 - Rizal Rahmawan (JUDICIOUS, 2020)
This study aims to analyze the significance of differences in stocks' performance that are members of the LQ45, especially in the mining sector. Researchers use the method based on their classification in development research. From the level of sluggishness, this study includes experiments with quantitative data in the form of company performance ratios summarized by researchers from the official IDX website, including Return non-equity (ROE), non-asset returns (ROA), Gross Profit Margin (GPM), Operating Profit Margin (OPM), Nett Profit Margin (NPM), and Earning Before Tax ( RBT). The researcher conducted a normality test on the data for four years and then performed a parametric difference test with the SPSS test tool and the One Way Anova analysis technique. This study indicates the research data is usually distributed with the average yield of superior stocks is PT. Bukit Asam, each variable calculation has an average height value with a standard deviation lower. The tests' results depending on entire ratio calculations, showed a difference significant between the stock to stock other. This shows the significance of the difference between one stock and another. One stock's advantage is proven to provide significant portfolio value for investors and other stakeholders.